Pengembangan Tes Potensi Keberhasilan Akademik pada Mahasiswa Program Studi Bimbingan dan Konseling - Adi Atmoko (JURNAL KONSELING GUSJIGANG, 2020)
This study aims to develop a valid and reliable instrument to measure the potential cognitive abilities of students to predict academic success in Counseling Guidance Study Program students. The research was carried out using test development methods starting from the conceptualization of tests, writing, and reviewing test items, field trials, and analysis of test results. The trial was carried out on 83 students of the Guidance and Counseling Study Program. The data were analyzed classically to determine the level of difficulty, discriminating power, and distractors of questions, item validity, and test reliability. Fifty-five items that were reassembled consisted of aspects of verbal analogy with 10 items, numerical 7 items, verbal logic with 11 items, analytical thinking 7 items, problem-solving skills 10 items and spatial abilities 10 items. Assembled questions consist of 37 items that have a validity of more than equal to 0.3 and 18 items that have a validity coefficient of 0.24 to 0.29. The consideration was that because the 37 items did not meet the target, 18 items were added which were revised based on the results of the analysis of the level of difficulty, differentiating power and distractors. From these 55 items, a reliability coefficient of 0.884 was obtained which was classified as high.